Liveability planning for cities: Within the Islamic framework of Maqasid Al-Shari’ah - Md Dali, Norimah; Abdullah, Alias; Ahmad Sarkawi, Azila (Malaysian Institute of Planners, 2016)
Liveability Planning is a new dimension of town planning practice. Town planning in Malaysia has been very physical and policy-biased. The soul component of liveability, quality of life and sustainability has been lacking. That is why environmental problems have now become the order of the day making urban living unhappy. Indeed liveability, quality of life and sustainability is one continuous process; a continuum. Conventional liveable indicators seem to concentrate more on economic and social wellbeing and lack religious elements. This gap is thought to be the missing link disabling human beings to live in harmony with nature. This research engages in the combined methodology which involves Focus Group Discussions, Interviews and Perception surveys in the formulation of the liveable city planning methodology based on Maqasid Al-Shari'ah (objectives of the Islamic Laws). Liveability planning practice that incorporate Maqasid into the conventional liveability indicators will render cities more liveable in the future.